2012
DOI: 10.1155/2012/687018
|View full text |Cite
|
Sign up to set email alerts
|

Goal-Directed Fluid Therapy Using Stroke Volume Variation Does Not Result in Pulmonary Fluid Overload in Thoracic Surgery Requiring One-Lung Ventilation

Abstract: Background. Goal-directed fluid therapy (GDT) guided by functional parameters of preload, such as stroke volume variation (SVV), seems to optimize hemodynamics and possibly improves clinical outcome. However, this strategy is believed to be rather fluid aggressive, and, furthermore, during surgery requiring thoracotomy, the ability of SVV to predict volume responsiveness has raised some controversy. So far it is not known whether GDT is associated with pulmonary fluid overloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Minimally invasive technologies currently available to guide goal-directed fluid therapy include oesophageal Doppler, arterial waveform analysis, photoplethysmography, and bioimpedance. Some experiences in thoracic surgery have been made using arterial waveform analysis targeting dynamic markers of preload responsiveness such as stroke volume variation (SVV), pulse pressure variation (PPV) and stroke volume index (SVI) (49)(50)(51). The accuracy of SVV and PVV are influenced by the tidal volume given and chest compliance, which is affected during open chest surgery.…”
Section: Intravenous Fluids and Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Minimally invasive technologies currently available to guide goal-directed fluid therapy include oesophageal Doppler, arterial waveform analysis, photoplethysmography, and bioimpedance. Some experiences in thoracic surgery have been made using arterial waveform analysis targeting dynamic markers of preload responsiveness such as stroke volume variation (SVV), pulse pressure variation (PPV) and stroke volume index (SVI) (49)(50)(51). The accuracy of SVV and PVV are influenced by the tidal volume given and chest compliance, which is affected during open chest surgery.…”
Section: Intravenous Fluids and Outcomementioning
confidence: 99%
“…EVLW has been used as a predictor for the development of acute lung injury in patients after thoracotomy. Recently, Haas et al showed that a GDFT algorithm using SVV did not increase extravascular lung water (EVLW) in patients undergoing thoracotomy for lung resection and oesophagectomy suggesting the safety of use of such protocols (49). Unfortunately no large prospective outcome studies have been done as yet and especially the utility of these markers with surgery by means of thoracoscopy is unknown.…”
Section: Intravenous Fluids and Outcomementioning
confidence: 99%
“…Another potential limitation in the thoracic surgical setting is the influence of distribution of lung perfusion by position and lung collapse: a spurious increase in measured EVLW has been noted due to regional alterations of pulmonary blood flow [95]. A study assessing a goal-directed approach to fluid management for thoracic surgery requiring lateral thoracotomy and OLV found that their strategy, fluid management guided by SVV, did not result in pulmonary fluid overload as assessed by PiCCO EVLWI [96].…”
Section: Early Detection Of Pulmonary Edemamentioning
confidence: 99%
“…One study has shown that GDT is at least not deleterious or does not result in pulmonary fluid overload when used for thoracic surgery requiring lateral thoracotomy and OLV [52]. While changing from the supine to the reverse Trendelenburg or prone positions significantly alters SV and thus SVV, 30° left or right recumbent and supine positions do not appear to affect SV or SVV measurements [53].…”
Section: Fluid Therapy -Goal Directed Therapy For Thoracic Surgerymentioning
confidence: 99%